The mystery of the butterfly bush Buddleja davidii: How are the butterflies attracted? - Lehner, Simon; Schulz, Stefan; Dötterl, Stefan (Frontiers in Plant Science, 2022)
Many plant species are pollinated by butterflies. These insects are primarily attracted by visual flower cues, however, butterflies are also known to respond to flower scents and some butterfly-pollinated plants are strongly scented. One of such plants is the butterfly bush, Buddleja davidii, which is a magnet for butterflies. It is widespread in its native region in Asia and famous for its success in invasive spreading in regions throughout the world. Due to its attractiveness to butterflies and its beautiful and conspicuous inflorescences, it also is an important ornamental, found in many gardens. Here, we elucidated the signaling between the butterfly bush and one of its abundant visitors, the peacock butterfly (Aglais io), using chemical and behavioral approaches. We found that olfactory cues are more attractive than visual cues, and that feeding behavior is only elicited by olfactory cues, most effectively by 4-oxoisophorone and oxoisophorone epoxide. The latter compound was not known to elicit behavioral responses in pollinators before this study. The relative importance of olfactory cues was higher in our study than previously observed in any butterfly pollination system. The identified attractants might contribute to the widespread occurrence of the butterfly bush in its native region in Asia and its success in invasive spreading in regions throughout the world.